Nanochemistry through self-assembly : polymerisation of the organised phases of polyelectrolyte-surfactant complexes - Ganeva, Desislava Evgenieva (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2003.